NERACA HARA NITROGEN SEBAGAI INDIKATOR PERTANIAN BERKELANJUTAN - Riyo - Samekto (Innofarm:Jurnal Inovasi Pertanian, 2011)
Abstracts Sustainable agriculture is the continuous production of food and fibre into the future while conserving the health of natural resources on and off the farm. It is important to find indicator as a tool to monitoring sustainability. There are two main methods of budgeting the nutrients balance of regional and national agricultural systems: soil-surface and farm-gate (OECD and EuroStat 2007; Oenema et al., 2003). The purpose of the paper is to discuse the importance of nitrogen balance as an indicator of agricultural sustainability and to propose the methods expalined by Viet-Ngu and Aluddin  (2009) as an alternative way to solve the defference of the two main methods. Key words: Sustainable agriculture, nitrogen balance, farm gate balance, soil surface balance.